(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The power system becomes non-linear as the usage of power electronics devices increases. These non-linear loads have the potential to draw and dissipate harmonic non-sinusoidal current and voltage at the association point with the utility. These non-sinusoidal currents and voltage are common, and they affect the power grid and harm consumer electronics. Hence, both customers and distributors of electrical power are now concerned about the power quality in power systems. To improve power quality and compensate for reactive power, shunt active power filters are utilized. The harmonic issue is discussed and analyzed in this book. The many traditional and modern harmonic solutions are described. The utilization of a shunt active power filter for harmonic current and reactive power compensation is contemplated. Different control strategies for active power filters notwithstanding unique harmonic extraction strategies are introduced and examined. self -tuning filter to improve the Shunt Active Power Filter‘s productivity on account of mutilated and unbalanced voltage system is introduced and talked about various shunt active power filter control systems are executed in MATLABand results are classified and examined.